PERBANDINGAN JUMLAH LEUKOSIT YANG DIHITUNG MENGGUNAKAN MODIFIKASI AIR PERASAN BUAH JERUK KUNCI (Citrus microcarpa Bunge) DAN LARUTAN TURK - Aristoteles; Denny Juraijin (IKesT Muhammadiyah Palembang, 2023)
Background : Laboratory tests, especially hematology, are frequently requested by doctors to help make a diagnosis. White blood cells (leukocytes) are an important part of the body’s defense system whose function is to fight infection causing microorganisms, tumor cells, and harmful foreign substances. Counting the number of leukocytes by manual method is done by diluting the blood using Tur ation, but the problem is that sometimes the Turk solution is not available. or is available but has expired, so an alternative is done by modifying key orange. juice (Citrus macrocarpa Bunge). Research purposes : To determine the difference in the number of leukocytes counted using modified key lime juice (Citrus microcarpa Bunge) and Turk solution. Research Methods : Experimental this research was conducted on January 19, 2023 at Bunda Hospital Palembang. and sampling was carried out at the IkeST Muhammadiyah Palembang Hematology Laboratory, totaling 31 EDTA blood samples. Results : The results obiained in this study showed that there was a difference in the leukocyte count with the modification of key orange juice (Citrus macrocarpa Bunge), turk solution, and a hematology analyzer. The results of the research data were carried out using data analysis with the SPSS program with the Shapiro–Wilk normality test and continued with the Kruskal test. Conclusion : There is a difference between the leukocyte count examination using modified key lime juice (Citrus macrocarpa Bunge) and Turk solution.